Угрюм-река: роман / Вячеслав Шишков - Шишков Вячеслав Яковлевич (АСТ, 2021)
Экземпляры: ФИЛ (20220419) / Инвентарный номер: 1118806 / Цена: / Сис.шифр: 84(2) / Авт.знак: Ш 65 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4